Altered Chemokine Th1/Th2 Balance in Addison’s Disease: Relationship with Hydrocortisone Dosing and Quality of Life - Ekman, B.; Alstrand, N.; Bachrach-Lindström, M.; Jenmalm, M. C.; Wahlberg, J. (Hormone and Metabolic Research, 2014)
The adrenalitis found in autoimmune Addison’s disease (AAD) is considered having a Th1-driven pathogenesis. Circulating Th1- and Th2-associated chemokines responsible for the trafficking of leukocytes to inflammatory sites are markers for the Th1/Th2 balance. The aim of the study was to assess if the same daily hydrocortisone dose of 30 mg given in either 2 or 4 doses to patients with AAD could affect the Th1/Th2 balance of circulating chemokines.Fifteen patients (6 women) with AAD were included in this randomised, placebo controlled, double blind cross-over study. Samples for chemokines, Th1-associated (CXCL10, CXCL11) and Th2-associated (CCL17, CCL22), were drawn 5 times during a 24-h period at the end of each treatment period and analysed with Luminex. Seven control subjects did the same diurnal blood sampling once. Subjects with AAD had higher median diurnal levels of the Th1-associated chemokines than controls, CXCL10 [43 (33–56) pg/ml vs. 22 (19–34) pg/ml, p<0.01] and CXCL11 [37 (29–48) pg/ml vs. 16 (9–24) pg/ml, p<0.001], whereas no significant difference was found regarding the Th2-related chemokines. Similar chemokine levels were found when the same hydrocortisone dose of 30 mg was divided in 2 or 4 doses. Levels of CXCL11 correlated negatively with scores of SF-36 domains (high score indicate better health) of General Health (GH) and total score for Physical Component Summary (PCS), and these negative correlations were most pronounced at 04:00 h on the 2-dose regimen. Patients with AAD have a dominant Th1 chemokine profile that partially correlates to reduced quality of life.
Keywords: adrenocortical insufficiency; cortisol; chemokines; autoimmunity